Public Service Transformation Through E-Government in the Klampid New Generation Application at the Department of Population and Civil Registration of Surabaya City - Dimas Rahmatullah; Amirul Mustofa; Sarwani Sarwani; Dian Ferriswara (International Journal of Humanities and Social Sciences Reviews, 2026)
The transformation of public services through information technology has become one of the government’s strategies to improve service quality for the community. The implementation of e-government enables public services to be delivered more effectively, efficiently, transparently, and with easier access. This study aims to analyze the transformation of public services through the implementation of e-government in the KLAMPID New Generation application at the Department of Population and Civil Registration of Surabaya City. The study employs a qualitative approach with a Case Study paradigm. Data were collected through interviews, observations, and documentation involving government officials and the public as service users. The research analysis uses the e-government development stage model proposed by Karen V. Layne and Jungwoo Lee, which includes the stages of presence, interaction, transaction, and transformation. The results indicate that the implementation of the KLAMPID New Generation application has supported the transformation of population administration services in Surabaya City. At the presence stage, the application provides digital information on population administration services. At the interaction stage, the system enables communication between the public and service providers through features such as notifications and service status monitoring. At the transaction stage, the public can submit service requests online by uploading required documents via the application system. Meanwhile, at the transformation stage, the KLAMPID New Generation application has integrated various population administration services into a single digital platform.